2018
DOI: 10.3389/fimmu.2018.00874
|View full text |Cite
|
Sign up to set email alerts
|

Silicosis and Silica-Induced Autoimmunity in the Diversity Outbred Mouse

Abstract: Epidemiological studies have confidently linked occupational crystalline silica exposure to autoimmunity, but pathogenic mechanisms and role of genetic predisposition remain poorly defined. Although studies of single inbred strains have yielded insights, understanding the relationships between lung pathology, silica-induced autoimmunity, and genetic predisposition will require examination of a broad spectrum of responses and susceptibilities. We defined the characteristics of silicosis and autoimmunity and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 39 publications
3
45
0
1
Order By: Relevance
“…The concentration of SiO 2 in human MDM (25 µg/cm 2 ) was similar to previous studies evaluating the impact of SiO 2 on alveolar M (40). The concentration of SiO 2 used in vivo (1.5 mg/mice), although lower than the concentrations used in mouse models of silicosis (2.5 to 10 mg/mice) (41)(42)(43), was able to induce granuloma formation (data not shown). We can thus hypothesize that the observed defect of efferocytosis at 1.5 mg/mice may also occur with higher concentrations of SiO 2 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The concentration of SiO 2 in human MDM (25 µg/cm 2 ) was similar to previous studies evaluating the impact of SiO 2 on alveolar M (40). The concentration of SiO 2 used in vivo (1.5 mg/mice), although lower than the concentrations used in mouse models of silicosis (2.5 to 10 mg/mice) (41)(42)(43), was able to induce granuloma formation (data not shown). We can thus hypothesize that the observed defect of efferocytosis at 1.5 mg/mice may also occur with higher concentrations of SiO 2 .…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, in mouse models of SLE, ROCK1/2 are spontaneously up-regulated and Y27632 significantly reduces serum levels of pro-inflammatory cytokines. Efferocytosis and activation of RhoA/ROCK could represent a key pathogenic process at the crossroads of systemic autoimmunity, M and silica exposure: in mouse models of SLE, SiO 2 inhalation is associated with more severe visceral manifestations of the disease and higher levels of ANA (43,49,50). ANA produced after SiO 2 exposure specifically target apoptotic cells (51) and an altered efferocytosis after SiO 2 inhalation could lead to an excess of uncleared apoptotic cells with subsequent increased production of these ANA.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include similarities between mice and people in IFN-␥ pathways that are important in human MSMD syndrome immu-nodeficiencies (33) and in the roles of type 1 interferons and neutrophils in disease progression (11,49). Studies using DO mice have already advanced the discovery of genes involved in autoimmune silicosis (50), in a wide range of immunological features (51), and in viral infections (52). To date, this resource has not been much used in bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies have shown lipid peroxidation, oxidative stress, an increase in IgM, serum IgG and the presence of ANA in mice exposed to silica, supporting its role as an adjuvant of T lymphocytes and as a possible factor triggering autoimmune diseases such as SLE and glomerulonephritis [97].…”
Section: Likely Essential Elementsmentioning
confidence: 91%